Architectural and decorative remains from the 16th and 17th centuries: An example of a house with an angled corridor in Old Damascus - Fayyad, Imane (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Among the very old, often poorly preserved if not damaged, domestic houses in Damascus, the al-Ḥakīm residence is probably one of the richest, with a very rich architectural and ornamental complex.